Curriculum Merdeka Analysis to Minimize Learning Loss in the Perspective of Education Practitioners - Kartika Hudayana; Imam Mujahid; Adlan Alif; Ula Nabila (STIT Fatahillah, 2023)
Learning loss is a concept that is interpreted as not maximizing the results of the learning process that takes place in schools. The Kurikulum Merdeka (Independent Curriculum) is a program that is expected to restore learning. This research uses qualitative methods with a descriptive approach. This study used research instruments like interviews, literature reviews, and documentation to gather data from the field. Furthermore, triangulation is used to test the data's validity. As a result of this investigation, the infrastructure and facilities that are currently available are inadequate. The Kurikulum Merdeka is hindered by a variety of factors, including the first being the poor quality of human resources, the second being the lack of adequate infrastructure and learning resources, the third being the three teachers' comfort with the current curriculum, and the fourth being the lack of experience with independent learning.